Employee Engagement Dynamics in High School Education: Investigating Influential Factors Across Contexts at a Ghanaian Institution - Apeadido, Shine; Alomenu, Clemence (Asian Journal of Interdisciplinary Research, 2024)
Employee engagement, a key element of organisational success, is influenced by various factors. However, there is limited clarity on how these factors impact employee engagement in high schools, particularly within the Ghanaian context. Hence, this study investigated perceived influential factors of employee engagement among high school teachers at Opoku Ware School in Ghana and their varying levels of influence across contexts using a structured survey administered to teachers (n = 75). Data analysis involving descriptive and inferential statistics, specifically ANOVA, was conducted to examine relationships between variables and test hypotheses. Key findings indicate that the employees have moderate engagement levels (M = 3.3), which are significantly impacted by leadership style, organisational culture, professional development, work-life balance, and recognition and rewards, with leadership style emerging as the most influential factor (M = 4.0). Furthermore, the analysis revealed significant differences in engagement factors across different departments (p < 0.05) and levels of seniority (p < 0.05), indicating that targeted interventions are required to address the diverse needs of teachers. However, unique results uncovered a consistency in leadership style (p = 0.33) across departments, and organisational culture (p = 0.81) and work-life balance (p = 0.76) across levels of seniority, suggesting the widespread potential impact of these specific factors. The study’s findings aligned with existing research and theories on employee engagement, emphasising the universal importance of the influential factors in driving engagement and offering valuable insights into ways high schools can enhance teacher engagement.